The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/anie.201103851
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Near‐Infrared Luminescent Lanthanide Host(Host–Guest) Complexes With a Metallacrown Sandwich Motif

Abstract: Oscillators omitted: A self‐assembled inclusion complex between a LnIII[12‐metallacrown‐4]23+ sandwich motif (green and bronze) and a [24‐metallacrown‐8] (purple) is stable in methanol. The YbIII complex has a large quantum yield (0.89 %) and luminescent lifetime (14 μs) in methanol, which are attributed to the exclusion of high‐energy oscillators from within 6.7 Å of the emitting YbIII ion by the metallacrown topology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
137
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(138 citation statements)
references
References 61 publications
(29 reference statements)
1
137
0
Order By: Relevance
“…Pecoraro et al reported that one of the important parameters to suppress vibrational relaxation was the distance between the lanthanide ion and the highly oscillated functional groups. [40] We have focused on the carbonyl group, which is the closest group to the lanthanide ion. The IR spectra of carbonyl groups for Eu(tmh)3(tppo) and Eu(hfa)3(tppo)2 are shown in Figure 6a.…”
Section: Resultsmentioning
confidence: 99%
“…Pecoraro et al reported that one of the important parameters to suppress vibrational relaxation was the distance between the lanthanide ion and the highly oscillated functional groups. [40] We have focused on the carbonyl group, which is the closest group to the lanthanide ion. The IR spectra of carbonyl groups for Eu(tmh)3(tppo) and Eu(hfa)3(tppo)2 are shown in Figure 6a.…”
Section: Resultsmentioning
confidence: 99%
“…These entities are of great interest for their aesthetically beautiful structures [2][3][4], unexpected transformations [5][6][7] and potential applications in magnetism [8][9][10], luminescence [11][12][13][14][15], catalysis [16][17][18], etc. Paramagnetic transition metal CCs are of intense interest and have attracted a vast amount of attention since the discovery that some CCs behave as single-molecule magnets (SMMs) [19][20][21].…”
Section: Introduction and Reviewmentioning
confidence: 99%
“…The frequency‐dependent ${\chi {^\prime}{^\prime}_{\rm{M}} }$ signals indicate slow relaxation of magnetization, which is typical of SMM‐like behavior. Tail‐like signals in the ${\chi {^\prime}{^\prime}_{\rm{M}} }$ versus T plots have also been seen for other [Mn 2 Ln 2 ] compounds 9. The characteristic maximum of the out‐of‐phase signal could not be observed, and presumably it may be below 1.8 K. We could not go further in the analysis of the slow relaxation process or the determination of the energy barrier and the time constant 32…”
Section: Resultsmentioning
confidence: 97%
“…Most of these MCs represent the 15‐MC‐5 structural type, mainly with Cu ions as ring metal ions,5c, 6 and only several cases displayed Ni ions in MC rings 7. Interestingly, 15‐MC‐5 complexes usually exhibited guest‐molecule recognition5c, 8 or served as building blocks for one‐dimensional solids 9. For instance, Ln[15‐MC‐5] compartments can recognize carboxylates with phenyl side chains of different lengths 8c.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation